Design of a new knee orthosis locking system : draft - Ramôa, Pedro Daniel Silva (2013)
The main goal of this work is to present the design process of a new mechatronic locking system for a Stance Control Knee Ankle Foot Orthosis (SCKAFO). The purpose of this solution is to support patients with gait disorders, namely for patients with muscular weakness and dystrophy in quadriceps femoris muscle group. The proposed mechatronic system has able to perform two main and distinct functions. The first one deals with the locking situation of the orthosis during the stance phase of human gait, in which contact between the foot and the ground occurs. The second function is associated with unlocking situation of the orthosis during the swing phase, in order to allow for the flexion motion of the knee. In this process, the fundamental kinematic and dynamic properties of the human gait with and without pathologies are considered. Thus, in the context of the present work sensors are used to detect the key phases that characterize the human gait, allowing for the correct system performance. These sensors are placed into anatomical relevant locations and allow the evaluation of the joint angles and accelerations during human gait. Then, the data collected by these sensors is interpreted by a microcontroller that controls the actuation system in order to lock or unlock the knee orthosis locking mechanism.Finally, a physical prototype is built and tested in an actual knee orthosis, which allows for its validation. From the preliminary results, it can be said that the model proposed here is innovative, safe, effective and functional. Moreover, the proposed model differs from the available commercial solutions in the measure that it is dynamic and does not require foot sensors to determine the human gait phases to define the lock/unlock.